Evaluating malaria risk projection under climate change scenarios in Senegal - Sambou, M. H. A.; Jampani, Mahesh; Panjwani, Shweta; Amarnath, Giriraj (Centre for Sexual Health and HIV AIDS Research (CeSHHAR), 2024)
The impacts of climate change on our planetary health pose a significant threat to various sectors, impacting more fragile economies and has far-reaching implications for public health. Malaria, a vector-borne disease in many parts of the world, remains a severe threat to human well-being. Moreover, malaria prevalence is anticipated to increase, as is the case with climate change, in the foreseeable future. The expected increase in the frequency of natural disasters, such as droughts and floods, is likely to create conducive environments for breeding diseasecarrying mosquitoes, thus exacerbating the spread of malaria. Thus, understanding the implications of climate change on malaria prevalence is of utmost importance, particularly for Senegal, a country in Sub-Saharan Africa where malaria is endemic. Senegal, located in West Africa, has a Sudano-Sahelian climate favourable to the proliferation of pathogens responsible for several diseases, including malaria. The spread of malaria is uneven throughout the country as a result of climatic zones and seasonal variations. While several studies have been carried out to quantify the associations between climatic factors and Malaria risk in Senegal, there are knowledge gaps in understanding the relationship between hydrometeorological conditions (such as extreme drought and extreme wet conditions) and malaria risk occurrence, as well as the delayed effects of these conditions on transmission. In this context, we quantified the association between hydrometeorological conditions (such as drought or flood) and malaria incidence and projected malaria risk related to climate for the future (2050) under different climate-change scenarios (SSP2.6, SSP4.5, SSP7.0, SSP8.5). To achieve these objectives, we employed a spatiotemporal Bayesian model with distributed lag non-linear models (DLNM) to explore the non-linear and delayed effects of hydrometeorological extremes on malaria risk across different regions of Senegal. Our findings highlight that the recorded malaria cases are strongly linked with hydrometeorological conditions. Specifically, we observe that dry and wet conditions, with a 2-month lag, were linked to an increased risk of malaria during 2016 and 2021. Furthermore, distinct variations in malaria risk trends were observed between the northern and southern regions of Senegal. Our results also project an increased risk of malaria in the northern part of Senegal (Sahel zone), especially in regions such as Dakar, Thies, and Louga, where conditions are expected to become more humid. Conversely, a decrease in malaria risks is anticipated in the southern regions of Senegal, such as Tambacounda, Kedougou, and Kolda, which are projected to experience mild drought conditions. Overall, these results will help stakeholders develop adaptation and mitigation plans to reduce future malaria risks in Senegal. The results of this study can be improved and adapted as a baseline for anticipatory action for malaria control strategies.